SMALL AND MEDIUM ENTERPRISES MANAGERS' RATING OF SKILLS N E E D E D B Y B U S I N E S S E D U C AT I O N G R A D U AT E S F O R ENTREPRENEURIAL SUCCESS IN ONDO AND EKITI STATES (NAU Journal of Technology and Vocational Education, 2024)
This study was necessitated by the need to ascertain whether business educationgraduates acquire adequate skills for entrepreneurial success by determining small andmedium enterprises managers' ratings of such skills needed by business educationgraduates for entrepreneurial success in Ondo and Ekiti States. Two research questionsguided the study and two hypotheses were tested. The design of the study was descriptivesurvey. The population for the study was 540 managers out of which 230 were sampled. Astructured questionnaire having five point rating scale which was duly validated by expertsin the field was used to collect data. Test re-test method was used to determine thereliability of the instrument and application of Cronbach Alpha for the internal consistencyyielded an overall reliability coefficient of 0.75. Mean and standard deviation were used toanalyze data in respect of research questions and to determine the cohesiveness orotherwise of respondents' ratings. The z-test was used to test the hypotheses at 0.05 levelof significance. Findings revealed that small and medium enterprises managers ratedproblem-solving and marketing skills as the skills highly needed by business educationgraduates for entrepreneurial success in the area. Based on these findings, it wasrecommended among othersthat government and professional body such asAssociation ofBusiness Educators ofNigeria (ABEN)should float training programmes such as workshops,seminars and conferences on the skills needed for entrepreneurial success to build andenhance the capacity of business teachers, business education students, businesseducation graduates, entrepreneurs and general public at regularintervals.